Spatio-Temporal Neural Changes After Task-Switching Training in Old Age - Dörrenbächer, Sandra; Schütz, Chiara; Woirgardt, Marc; Wu, C. Carolyn; Zimmer, Hubert D.; Kray, Jutta (Frontiers in Aging Neuroscience, 2019)
In the present study, we aimed at examining selective neural changes after task-switching training in old age by not only considering the spatial location but also the timescale of brain activation changes (i.e., sustained/ block-related or transient/ trial-related timescales). We assigned a sample of 50 older adults to a task-switching training or an active single-task control group. We administered two task paradigms, either sensitive to transient (i.e., a context-updating task) or sustained (i.e., a delayed-recognition working-memory task) dynamics of cognitive control. These dynamics were captured by utilizing an appropriate event-related or block-related functional magnetic resonance imaging design. We captured selective changes in task activation during the untrained tasks after task-switching training compared to an active control group. Results revealed changes at the neural level that were not evident from only behavioral data. Importantly, neural changes in the transient-sensitive context updating task were found on the same timescale but in a different region (i.e., in the left inferior parietal lobule) than in the task-switching training task (i.e., ventrolateral PFC, inferior frontal junction, superior parietal lobule), only pointing to temporal overlap, while neural changes in the sustained-sensitive delayed-recognition task overlapped in both timescale and region with the task-switching training task (i.e., in the basal ganglia), pointing to spatio-temporal overlap. These results suggest that neural changes after task-switching training seem to be critically supported by the temporal organization of neural processing.